2003
DOI: 10.1021/es025868z
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Volatility of Diesel Nanoparticles:  Chassis Dynamometer Experiments

Abstract: We analyzed the size-dependent volatility of nanoparticles in a diameter range of 30-70 nm in diesel exhaust emissions. The test system included a medium-duty diesel truck on a chassis dynamometer, a single-stage dilution tunnel, a tandem differential mobility analyzer (TDMA) equipped with an electric furnace, and a condensation particle counter. The size shifts of monodispersed diesel nanoparticles under changing furnace temperatures were measured by TDMA in the gas phase. Together with the reduction of avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 30 publications
5
40
0
Order By: Relevance
“…In general, PM2.5 emission factors were higher for higher average vehicle speeds, consistent with studies indicating higher PM emission rates observed under high engine load conditions (i.e., vehicle Table 1. speeds) (Kean et al, 2003;Cadle et al, 2007;Zavala et al, 2009b). Similarly, recent studies are consistent with the observation that fine PM emissions increase with engine load for diesel-powered engines and that volatile fraction of fine PM decreases with increasing load (Ziemmann et al, 2002;Kwon et al, 2003). This can be explained by the high fraction of unburned lubricating oil observed in the PM exhausts with respect to combustion oxidation products and unburned fuel.…”
Section: Pm25 Emissionssupporting
confidence: 73%
“…In general, PM2.5 emission factors were higher for higher average vehicle speeds, consistent with studies indicating higher PM emission rates observed under high engine load conditions (i.e., vehicle Table 1. speeds) (Kean et al, 2003;Cadle et al, 2007;Zavala et al, 2009b). Similarly, recent studies are consistent with the observation that fine PM emissions increase with engine load for diesel-powered engines and that volatile fraction of fine PM decreases with increasing load (Ziemmann et al, 2002;Kwon et al, 2003). This can be explained by the high fraction of unburned lubricating oil observed in the PM exhausts with respect to combustion oxidation products and unburned fuel.…”
Section: Pm25 Emissionssupporting
confidence: 73%
“…Kwon et al 27 used a medium-size diesel truck on a chassis dynamometer to study the volatility of UFPM. Particle size distributions were measured with a TDMA, where an electric furnace was connected to the exhaust to vary the temperature of the sampled UFPM, thereby influencing the volatilization of the UFPM compounds.…”
Section: ϫ3mentioning
confidence: 99%
“…Measurements of particle emissions from motor vehicles have been accomplished via dynamometer source testing (Chase et al 2000;Kwon et al 2003;Sakurai et al 2003aSakurai et al , 2003bSchauer et al 1999Schauer et al , 2002Suess and Prather 2002), roadway tunnel sampling (Allen et al 2001;Fraser et al 1998;Laschober et al 2004;McGaughey et al 2004), on-road chase experiments (Shah et al 2004;Vogt et al 2003), and roadside measurements Sturm et al 2003;Zhu et al 2002aZhu et al , 2002bZhu et al , 2004. In general, particles directly emitted from motor vehicles are in the size range from 20 to 130 nm in aerodynamic diameter for diesel engines and from 20 to 60 nm for gasoline engines (Ristovski et al 1998).…”
Section: Introductionmentioning
confidence: 99%